Implementation of Analytic Hierarchy Process Method In the Decision Support System for Selecting Department in University - Syahida Nurhidayarnis; Anisa Putri; Raja Zaid Ibnu Zarier Ismail; Meisya Delila Br Ginting; Walovi Lestari Nurrafa (IJATIS: Indonesian Journal of Applied Technology and Innovation Science, 2024)
Every year, high school graduates show a strong desire to pursue higher education. However, many of them experience limitations in choosing a Department or study program, creating the "Wrong Department" phenomenon and facing a serious dilemma. The selection of a Department in the Faculty of Science and Technology is considered a crucial stage in the academic journey. Errors in decision-making not only affect students' career development, but also have implications for their contribution to the progress of society and the world. In this case, a systematic and measurable approach is needed to provide assistance to prospective students in making the right decision in choosing a Department. Decision Support System (DSS) becomes a crucial instrument in overcoming the complexity of the decision-making process. One method that is often applied in DSS is the Analytic Hierarchy Process (AHP). AHP helps to explicitize key factors through the formation of a hierarchy of relevant criteria, but in situations of uncertainty, Fuzzy Logic is integrated. Fuzzy Logic allows handling data uncertainty by modeling it as a membership variable in a set. The results of this study show that the most influential criteria in choosing a Department are interest and talent.